Anxiety and depressive symptomatology among children and adolescents exposed to the COVID-19 pandemic – A systematic review - Djurdjević, Sanja; Conde Ghigliazza, Ileana; Dukanac, Vesna; Djurdjević, Ana (Vojnosanitetski pregled, 2022)
Background/Aim. Children and adolescents are sensitive groups for the development of mental disorders during the crisis. The aim of this systematic review was to assess the impact of the COVID-19 pandemic on anxiety and depressive symptomatology in the population of children and adolescents. Methods. The investigation was based on a systematic review followed by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, including Ovid MEDLINE, Embase, Global Health, and APA Psyc Info databases, to identify relevant studies reporting anxiety and depressive symptoms among children and adolescents during the COVID-19 pandemic. A total of 27 articles were included. Results. Anxiety symptoms increased from 28.3% before the pandemic to 49.5% during confinement [General Anxiety Disorder (GAD)-7 ≥ 11)] (McNemar test, p
Keywords: adolescent; anxiety; child; covid-19; depression.